Participação de associados em cooperativas agrícolas do estado de Sergipe - Carvalho da Cruz, Johil Antônio; G Francis, David; Lima Thiébaut, José Tarcísio; Machado Filho, Francisco (Revista Ceres, 2025)
This study examines participation among members of five agricultural cooperatives in the State of Sergipe. The respondents were randomly chosen from those who had been members for at least two years (since 1976).